Perception of Universitas Padjadjaran Students towards Psychotic Disorders - Rusly, Renzavaldy; Pandia, Veranita; Sunjaya, Deni Kurniadi (Althea Medical Journal, 2018)
Background: Psychotic disorders have a very high incidence in Indonesia and arethe first rank in terms of the global burden of disability. Students are the frontline in the face of society. The formation of stigma and discriminationÂ  is rooted fromÂ  bad perceptions. The aim of this study was to determine and measure Universitas Padjadjaran studentsâ perceptions towards psychotic disorders and find out why these perceptions can be shaped. Methods: The design of study was a sequential explanatory mixed method research. The population of this study is glittering Universitas Padjadjaran students who were in Jatinangor between batches 2011 to 2013. Samples were taken using cluster and stratified random sampling. Quantitative data retrieval was collected by using a self-administered questionnaire. Next, there would be focused group discussions and in-depth interviews which discussed the results of the quantitative data collection then interpreted them qualitatively. Result: The percentage of students at Universitas Padjadjaran with perception of psychotic disorders in good category was 19.04%, 80.96% unfavorable category, and bad 0% (n=126). Besides various relevant opinion found why these perceptions were formed, such as a lack of education on students towards psychotic disorders, the existence of stigma based on life experience of psychotic patients, the lack of social media and physical campaign towards the psychotic disorders.Conclusions: The perception of Universitas Padjadjaran students towards psychotic disorders is still relatively unfavorable, therefore literation towards psychotic disorders should be provided through education, campaigns, social media utilization by psychiatrists and the government.